Financial Performance Analysis With Profitability Ratios (Study On Sari Tahu Business in Puuwatu Village Puuwatu District, Kendari City) - Al-Hikmah Nur; Yusna Indarsyih; Fahria Nadiryati Sadimantara (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the analysis of financial performance with profitability ratios in the home industry (Study on Sari Tahu Business in Puuwatu Village, Puuwatu District, Kendari City). The research location was determined purposively (purposive) with the consideration that the Sari Tahu business in the Puuwatu Village is one of the businesses that is quite profitable.develop. The sample in this study was the home industry of Tofu Sari Business in Puuwatu Village, Kendari City with the business owner as the informant. Data were analyzed using Microsoft Excel to determine profit and loss statements, balance sheets, and analyze financial ratios. Financial ratio analysis is done by looking at the comparison of profitability ratios using Net Profit Margin and Return on Investment. The results showed that the financial performance of the Sari Tahu household industry from 2018-2021 obtained financial performance with good criteria because the percentage value was above 15%. It's a different case, with the Return on Investment (ROI) value which has decreased from 2018-2021 but is still in the pretty good category